Alice in Wonderland - Carroll, Lewis (Italy ELI -Young Readers, 2009)
The classic story of a young girl who falls into a hole, eats and drinks poison and grows bigger and smaller.
Picture dictionary. Games and language activities.
Keywords: Story; Classroom activities; Adventure; Pre-Intermediate Level